Effects on carcass traits of beef ration energy level and length of feeding - Allen, Dell M.; Hunt, Melvin C.; Kropf, Donald H.; Harrison, A.R.; Brent, B.E.; Riley, Jack G.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2011)
We used 150 Angus yearling steers of similar background from the Livestock and Meat Industry Council cattle-flow project. Each was assigned to one of the 12 treatments (10 per treatment) involving low-, medium-, and high-energy rations (calculation to supply 34, 45, and 58 megacalories per 100 lbs. ration for net energy of production). Times on rations were 56, 91, 119, 147, and 175 days. Ten steers were fed a submaintenance ration of prairie hay 28 days before slaughter, and 10 served as controls (slaughtered when study started).
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Carcass traits; Ration; Energy